2023
DOI: 10.1039/d3nr03618a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the thermomechanical behavior of graphene-reinforced conjugated polymer nanocomposites via coarse-grained modeling

Yang Wang,
Zhaofan Li,
Dali Sun
et al.

Abstract: By employing coarse-grained (CG) molecular dynamics (MD) simulations, this study aims to investigate the thermomechanical behaviors of graphene-reinforced conjugated polymer nanocomposites at a fundamental molecular level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 89 publications
(143 reference statements)
1
13
0
Order By: Relevance
“…These results indicated that the mechanical behaviors of the CG model were not affected by the system size, which aligned with the findings of our previous study. 77…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that the mechanical behaviors of the CG model were not affected by the system size, which aligned with the findings of our previous study. 77…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the mechanical behaviors of the CG model were not affected by the system size, which aligned with the findings of our previous study. 77 As mentioned in the previous discussion, hu 2 i is widely recognized as a metric for assessing the local free volume within the polymer system. 52,78 Consequently, it inversely serves as an indicator of the local molecular stiffness.…”
Section: Validation Of Cg Pdms Modelmentioning
confidence: 99%
“…The detailed AA and CG simulations for obtaining the bonded and nonbonded interactions can be found in the Supporting Information and previous work. 25 The representative bonded probability distributions are shown in Figure 2. After 4−7 iterations of IBI, the bonded distribution of the CG model (symbol) is consistent with the target AA model, and the corresponding CG potentials are shown in the right y-axis in Figure 2.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the present work, following our previous ER coarse-graining framework, , we systematically explore the mechanical and conformational properties of P3AT thin film upon deformation using the chemistry-specific CG molecular dynamics simulation. Density and local mobility measurements showed a soft interfacial layer for all P3AT thin films with a thickness that does not depend on M w or side-chain length.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation